Looking for Justice in the Black Cloud: Providing Justice for Victims of Sexual Harassment in Indonesia (Semarang State University Undergraduate Law and Society Review, 2022)
According to Komnas Perempuan, sexual harassment is a sexual act through physical or non-physical touch that targets the sexual organs or sexuality of the victim. This includes using whistles, flirting, sexually suggestive speech, displaying pornographic material and sexual desires, touching or touching body parts, gestures or gestures of a sexual nature that cause discomfort, be offended, feel humiliated, and possibly cause health problems. and safety. The law also has its own interpretation of sexual harassment. In the Criminal Code (KUHP) there is no term sexual harassment, but in Article 289 to Article 296 of the Criminal Code it is called obscenity. R. Soesilo in the book “KUHP and its comments”, sexual harassment includes acts that violate a sense of decency, or other vile acts, and all of them are in an environment of sexual lust. For example, kissing, groping the genitals, groping the breasts and so on. The term sexual harassment, according to Ratna, refers to sexual harassment which is defined as unwelcome attention or legally defined as an imposition of unwelcome sexual demands or creation of sexually offensive environments.